The Guideline to Promote the Personal Administration in Accordance with the Four Brahmavihāra Dhammas of Private Schools under the Office of Education, Nong Bua Lam Phu Province - wichakul, kanthida; Jotivamso , Phrakhrupalad Boonchuay; Saikham, Sunthon (Journal of Modern Learning Development, 2021)
The objectives of this research were: 1) to study the guideline to promote the personal administration in accordance with the Four Brahmavihāra Dhammas (Sublime State of the Mind) of the private schools under the Office of Education, Nong Bua Lam Phu Province; 2) to present the guideline to promote the personal administration in accordance with the Four Brahmavihāra Dhammas of the private schools under the Office of Education, Nong Bua Lam Phu Province.by means of the mix research methodology. The samples in this study included 210 The target group included 10 of the administrators (5) and teachers (5). The obtained data were analyzed by the following statistics: Percentage, Mean and Standard Deviation. The research results were as follows: 1. The overall mean score of the strategic leadership of the school administrators in accordance with the Four Iddhipāda Dhammas under the Khon Kaen Primary Educational Service Area Office 2. The most practical aspect was seen in that of the revolutionary thinking, followed by that of prediction and future determination. The least practical aspect was seen in that of perceiving, understanding, holistically and strategically thinking. 2. The guidelines are as follows: 1) perceiving, understanding, holistically and strategically thinking, the administrators should recognize and understand to information related to administration to determine the direction of the organization; 2) creating a strategy with various imagination, administrators should take the information system to support in management give for teachers to participate in strategy formulation; 3) prediction and future determination, administrators should consider long-term results such as knowledge management, building a knowledge base to develop the school into a learning organization; 4) revolutionary thinking, the administrators should bring the PDCA process to improve the quality of the school to the full potential; 5) creating a vision, the administrators should set a vision linked to the present and the future and they must be a far-sighted person, consistent with needs and social change.